Evaluation of the operational efficiency of 3 MWp photovoltaic power plant situated in the Sahara Desert of Algeria - Chaib, Messaouda; Dahbi, Abdeldjalil; Benatiallah, Ali (Institute of Advanced Engineering and Science, 2024)
The primary aim of this study is to examine the behaviour of the photovoltaic plant installed in Kabertene, Algeria, under desert climate conditions. Simulations and modeling have been carried out for the photovoltaic cell, panel, and array under standard test conditions as well as a range of different operating conditions. Furthermore, the photovoltaic (PV) plant has been simulated using measured data, PVsyst, and MATLAB Simulink. The aim was to assess the solar energy potential within the examined geographic area and evaluate the performance of the PV plant. The performance of the obtained results was compared in different cases. The real results closely match those of PVsyst and MATLAB software when using real data and the real performance ratio, because it takes into consideration the cleanliness state of the PV panels. The results indicate that environmental factors, especially solar radiation and temperature, exert a considerable effect on the operational capacity of the PV system. This leads to variations in the electrical energy output and the performance ratio of the system. The total yearly energy injected into the grid was 5028.21625 MWh. The annual average daily PV system performance ratio is 67%. Finally, the research concludes that the area has substantial solar potential, encouraging the development of new PV plants.